ANALISISÃÂ KEBUTUHANÃÂ GURUÃÂ BIDANGÃÂ TEKNIKÃÂ MESINÃÂ MENURUTÃÂ PROGRAMÃÂ KEAHLIANÃÂ YANGÃÂ DIBUKAÃÂ DIÃÂ KOTAÃÂ SEMARANGÃÂ - Abdullah, -; SunyotoÃƒÂ‚Ã‚Â , -; YudionoÃƒÂ‚Ã‚Â , Heri (Jurnal Pendidikan Teknik Mesin, 2008)
Tujuan ÃÂ penelitian ÃÂ adalah:(1) ÃÂ untuk ÃÂ mengetahui ÃÂ berapa ÃÂ besar ÃÂ kebutuhan ÃÂ guru ÃÂ Bidang ÃÂ Teknik ÃÂ MesinÃÂ menurut ÃÂ Program ÃÂ Keahlian ÃÂ yang ÃÂ dibuka ÃÂ di ÃÂ kota ÃÂ Semarang, ÃÂ (2) ÃÂ untuk mengetahui ÃÂ rasio ÃÂ antara ÃÂ siswa ÃÂ dan ÃÂ guruÃÂ Bidang ÃÂ Teknik Mesin menurut ÃÂ Program ÃÂ Keahlian ÃÂ yang ÃÂ dibuka ÃÂ di ÃÂ kota ÃÂ Semarang, ÃÂ (3) ÃÂ untuk mengetahui ÃÂ berapaÃÂ proporsi guru Bidang Teknik Mesin pada tiapÃ¢â¬Âtiap sekolah, (4) untuk mengetahui kualifikasi guru Bidang TeknikÃÂ Mesin ÃÂ yang ÃÂ berhubungan ÃÂ dengan ÃÂ jenjang ÃÂ atau ÃÂ jenis ÃÂ ijazahnya, ÃÂ dan (5) untuk mengetahui relevansi ProgramÃÂ Keahlian Teknik Mesin dengan kebutuhan ÃÂ lapangan kerja (industri). Populasi dan sampel penelitian ÃÂ ini adalah 22ÃÂ SMK Bidang Keahlian Teknik Mesin di kota Semarang. Variabelnya adalah kebutuhan guru, rasio antara guru danÃÂ siswa, ÃÂ kualifikasi ÃÂ guru ÃÂ dan ÃÂ relevansi ÃÂ program ÃÂ dengan ÃÂ kebutuhan ÃÂ pasar. ÃÂ Metode ÃÂ penelitian ÃÂ ini ÃÂ menggunakanÃÂ metode dokumentasi dan angket. Data dianalisis dengan menggunakan rumus kebutuhan guru.Kata kunci: kebutuhan guru, teknik mesin, program keahlianÃÂ The purposes of this research are: (1) to discover how much the ÃÂ need ÃÂ for ÃÂ teachers ÃÂ of ÃÂ MechanicalÃÂ Engineering ÃÂ according ÃÂ to ÃÂ Skill Programs ÃÂ opened ÃÂ in ÃÂ Semarang City is, (2) to identify ratio between students andÃÂ teachers of Mechanical Engineering according to Skill Programs opened in Semarang City, (3) to find out how muchÃÂ the proportion of Mechanical Engineering Teachers in accordance with degree or its certificate type, and (5) to beÃÂ aware ÃÂ of ÃÂ relevance ÃÂ between Mechanical ÃÂ Engineering ÃÂ Skill ÃÂ Program ÃÂ and ÃÂ job ÃÂ vacancy ÃÂ (industry). ÃÂ Population ÃÂ andÃÂ sample ÃÂ of ÃÂ the ÃÂ research ÃÂ were ÃÂ 22 ÃÂ vocational ÃÂ high ÃÂ schools ÃÂ with ÃÂ their ÃÂ Mechanical ÃÂ Engineering ÃÂ Skill ÃÂ Program ÃÂ inÃÂ Semarang City. The variables were the need for teachers, ratio between teachers and students, teacher qualificationÃÂ and relevance between the program ÃÂ itself and market need. The research used documentation and questionnaireÃÂ method. Data was analyzed using the formula of the need for teachers.Keywords: the need for teachers, mechanical engineering, skill program